The RCK2 Domain Uses a Coordination Site Present in Kir Channels to Confer Sodium Sensitivity to Slo2.2 Channels - Zhang, Zhe (Society for Neuroscience, 2010)
Slo2 Na(+)-activated potassium channels are widely expressed in neurons and other cells, such as kidney, heart, and skeletal muscle. Although their important physiological roles continue to be appreciated, molecular determinants responsible for sensing intracellular Na(+) remain unknown. Here we report identification of an Na(+) regulatory site, similar to an Na(+) coordination motif described in Kir channels, localized in the RCK2 domain of Slo2.2 channels. Molecular simulations of the homology-modeled Slo2.2 RCK2 domain provided structural insights into the organization of this Na(+) coordination site. Furthermore, free energy calculations reproduced the experimentally derived monovalent cation selectivity. Our results suggest that Slo2.2 and Kir channels share a similar mechanism to coordinate Na(+). The localization of an Na(+) sensor within the RCK2 domain of Slo2.2 further supports the role of RCK (regulators of conductance of K(+)) domains of Slo channels in coupling ion sensing to channel gating.